Performa Model Tes Hidrolis Untuk PLTMH Head Rendah dengan Menggunakan Tekanan Aliran dan Kecepatan Pusaran Air (Vortex) - Suhartono Suhartono; Ratih Indri Hapsari; Mohamad Zenurianto; Ikrar Hanggara (Universitas Tribhuwana Tunggadewi Malang, 2020)
The development of human life is greatly influenced by the presence of electrical energi. Therefore it is necessary to conduct research related to the generation of electrical energi on a small scale (micro). One alternative electricity generation by changing the motion energi is done by utilizing the flow of water. Water flow with low discharge and head is easily found in several places, especially small rivers or irrigation channels. Utilization of low flow head and discharge is a great potential to be able to produce small-scale (micro) electrical energi. In this research, modeling of low flow and low head discharge will be carried out to find out how much potential the electrical energi can generate. There are 3 experiments namely water power, whirlpool, high fall. The variable that used in this experiment is various different head on the basin (in experiment 1; 0.2 meters, 0.3 meters, 0.4 meters, and 5 meters) to generate specific discharge that can make vortex flow and the velocity of the propeller from plunge flow. The methodes that used in this experiment is basic measurement using instrumental flow digital and setup flow using the valve. Experiment 1 with a head of 50 meters found 1,414 watts of water power with a discharge rate of 17.3 liters/minute on a 1